Neurologist and Neurosurgeon: A ‘Sine Qua Non’ in Paediatric Intracranial Pathology Management - Natalwala, Ammar; Gallo, Pasquale; Sokol, Drahoslav; Kandasamy, Jothy; Tallur, Krishnaraya Kamath; McLennan, Ailsa; Shetty, Jayakara; Chin, Richard; Baxter, Alex; Eunson, Paul; McWilliam, Kenneth; Kaliaperumal, Chandrasekaran (Biology, Engineering, Medicine and Science Reports)
Specialist care providers often treat complex, life-threatening intracranial paediatric pathologies and team-based clinical decisions by neurologists and neurosurgeons are vital for good clinical outcomes. We describe six scenarios highlighting multi-disciplinary team-based management of challenging paediatric conditions which provided successful outcomes. This work may aide future management of similar cases.
Keywords: Challenging paediatric cases; Neurology; Neurosurgery; Team-Based; Multi-Disciplinary